GAMBARAN MEKANISME KOPING PASIEN GANGGUAN PERSEPSI SENSORI - Nur Eka Dzulfaijah; Ainun Kurniati; Anas Makruf; Muhammad Affan (Akademi Kebidanan Harapan Bunda Bima, 2025)
The process of maintaining balance in the human body occurs dynamically where humans try to face all external challenges so that a state of balance can be achieved. Individuals who experience maladaptive social responses use a variety of mechanisms in an attempt to cope with anxiety. Schizophrenia is a neurological disease that affects a client's perception, way of thinking, language, emotions, and social behavior. Schizophrenia is often identified with hallucinations, and hallucinations are a symptom that is often found in clients with mental disorders. The aim of this study was to determine the coping mechanisms of schizophrenia patients with hallucination nursing problems undergoing intensive care in the Mawar and Angsoka rooms of RSJP NTB. This study uses a descriptive design, with the number of responses from sufferers of sensory perception disorders and hallucinations being 30 people. The data collection tool used a checklist. The results showed that 73% of respondents used maladaptive coping mechanisms and 26.7% of respondents used adaptive coping mechanisms. Therefore, ward nurses are expected to be able to help and support hallucinatory clients by increasing the use of adaptive coping mechanisms, in addition to providing counseling to families to help them use adaptive coping mechanisms.